Psychological Wellbeing Among South African Women with Endometriosis: A Quantitative Study - Ismail, Raeesah (University of the Witwatersrand, Johannesburg, 2025)
Endometriosis is a chronic illness that significantly impacts the physical, emotional, and psychological wellbeing (PW) of women. Despite its prevalence, the psychological toll of endometriosis remains under-researched, particularly in South Africa, where healthcare disparities and limited resources exacerbate challenges. The aim of this study addresses a critical gap in exploring the associative and predictive relationships between delayed diagnosis, psychosocial factors (participation in support groups and perceived medical support), and demographics (age and socioeconomic impact and access) on the experiences of PW in a sample of South African women diagnosed with endometriosis. Using a cross-sectional, correlational design, the study analysed 248 South African women aged 18–55 diagnosed with endometriosis. Participants were recruited via social media, support groups, and university students, employing non-probability sampling. Data was collected using the Ryff Psychological Wellbeing Scale, the Stellenbosch Endometriosis Quality of Life Scale (SEQOL), the Endometriosis Impact Questionnaire (EIQ), and a contextual questionnaire. Descriptive and inferential statistics, including Pearson correlations and regression analyses, were conducted. The simple regression results revealed that perceived medical support, EIQ Social Impact, SEQOL Support, socioeconomic status contextual burden, SEQOL Income, EIQ Employment & Financial and Education impact, and EIQ Psychological Impact and SEQOL PW were all significantly negative predictors of PW. However, delayed diagnosis, age, and support group participation were not found to be significant predictors. Additionally, the overall multiple regression model was significant (F(9, 238) = 8.81, p < .001) and accounted for approximately 25.0% of the variance in PW with socioeconomic contextual burden emerging as the only significant predictor of PW (p = .028). Socioeconomic Impact and Access factors accounted for the largest variance in PW, showing the role of healthcare access and financial strain. The two psychological factor measures also emerged as a key area affecting overall PW. The results emphasise the need for endometriosis awareness, integrating mental health support into treatment plans and addressing systemic barriers to healthcare. This research provides a foundation for future studies to leverage in studying South African women with endometriosis.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts (Psychology by Coursework and Research Report), to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: Age; Delayed diagnosis; Endometriosis; Psychological wellbeing; Psychosocial support; Socioeconomic impact and access; South Africa; SDG-3: Good health and well-being; SDG-10: Reduced inequalities